194 Lactulose and hydrogen-rich water protect against fusarium mycotoxin-induced intestinal injury in female piglets. (7th December 2018) - Ji, X; Zheng, W; Zhang, Q; He, J; Yao, W
Abstract: The Fusarium mycotoxins target the gastrointestinal tract which affects human and animal health. The objective of this study was to evaluate the effects of lactulose (LAC) and hydrogen-rich water (HRW) on intestinal injury in female piglets fed with mycotoxin-contaminated diets. A total of 24 individually housed female piglets with a mean body weight of 7.85 ± 0.84 kg were randomly assigned to receive 1 of 4 treatments (6 pigs/treatment) for 25 d: uncontaminated basal diet (NC), mycotoxin-contaminated diet (MC), MC diet + LAC (MC+LAC) and MC diet+ HRW (MC+HRW). On day 25, blood and different segments of small intestines samples were collected. The activity of serum diamine oxidase (DAO) and lipopolysaccharide (LPS), intestinal hydrogen levels, intestinal epithelial cells apoptosis status and intestine barrier integrity were measured. Results showed that both lactulose and HRW treatments significantly alleviated the adverse effects of mycotoxins on intestinal integrity. Moreover, compared to MC group, both LAC and HRW affected genes expression related to apoptosis and tight junction. In addition, both LAC and HRW also significantly increased the protein expression of claudin-3(CLDN3) compare to the MC group and attenuated the irregular cellular distribution of CLDN3 in the small intestine caused by the mycotoxins. Most importantly, HRW also increased the hydrogen concentrations in the small intestine. Collectively, these results suggested that both LAC and HRW exerted protective roles on the intestinal injury in piglets fed with mycotoxin-contaminated diets.